Monetary Policy Challenges - Vieira, Carlos (My University, 2005)
The profound changes in the economic environment surrounding monetary policy are challenging monetary authorities. More global and more complex economic and financial systems defy monetary policy with further uncertainties. The objective of this study is to examine the long run modifications resulting from these challenges, and confront the distinct views on how to deal with them. The interest on this subject has been recently revived with the success of monetary policy in reducing and maintaining low levels of inflation, and the failure of Japanese authorities to prevent and escape deflation and the consequent recession.
Keywords: monetary policy